Spin-orbit coupling affecting the evolution of transverse spin - Eismann, Joerg S.; Banzer, Peter; Neugebauer, Martin (Physical Review Research, 2019)
We investigate the evolution of transverse spin in tightly focused circularly polarized beams of light, where spin-orbit coupling causes a local rotation of the polarization ellipses upon propagation through the focal volume. The effect can be explained as a relative Gouy-phase shift between the circularly polarized transverse field and the longitudinal field carrying orbital angular momentum. The corresponding rotation of the spatial distribution of the electric transverse spin density is observed experimentally by utilizing a recently developed reconstruction scheme, which relies on transverse-spin-dependent directional scattering of a nanoprobe.
CRIS-Team WoS Importer:2021-10-18